Editorial - Modin, Madeleine (Puls – musik- och dansetnologisk tidskrift, 2025)
This year, we have tested transitioning Puls – Journal for Ethnomusicology and Ethnochoreology to a continuous publication model. As a result, Volume 10 has been divided into two separate releases: the first set of articles, reviews, and reports was published in May, and the remainder is now in December. The editorial routines required to maintain multiple stages of the publication process simultaneously are still under development, and the editorial team has found this approach to have both advantages and drawbacks. We hope that the opportunity to submit manuscripts at any time throughout the year, along with more frequent publication windows, will be seen as an improvement by our authors. As always, the articles in this volume engage with ethnousicology and ethnochoreology in their broadest disciplinary sense. The scope spans topics such as an in-depth analysis of traditional Norwegian springar dance, an exploration of cognitive experiences during jazz improvisation, early schlager lyric translations, the transmission of ritual dances in Romania, music and song in the Swedish women’s suffrage movement, and the publication of fiddle music tune books in 1950s Sweden. The decision to posthumously publish an older article by Anca Giurchescu and Owe Ronström was made after careful consideration and discussion, motivated by its continued relevance in light of ongoing debates surrounding UNESCO’s designation of intangible cultural heritage and the interventions into living cultural practices that it often entails. The fieldwork was conducted and the article written prior to the Romanian Căluş tradition being granted this status in 2008. In his introduction to the article, guest editor Owe Ronström provides further context regarding the ethnographic fieldwork and the subsequent development of the article. Alongside the article and its introduction, we also publish a documentary film produced as part of this research, an example of the possibilities admitted by the online format. As Editor in Chief, I would like to extend my sincere thanks to everyone who contributed to making this volume possible. First and foremost, I thank the authors, who have patiently endured the exhaustive editorial process. I also wish to acknowledge the anonymous peer reviewers, proofreaders, and designers. Special thanks go to the editorial team, particularly our external collaborators who work outside the remit of Svenskt visarkiv’s government mandate: PhD Mathias Boström, our new editor for reviews and conference reports, and Professor Owe Ronström, whose dedication and expertise as guest editor over the past three issues of Puls have been invaluable. Madeleine Modin Editor in Chief